ANALISIS FAKTOR – FAKTOR PRODUKSI BUDIDAYA IKAN LELE (Clarias batrachus) DI KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This study aims to analyze the factors that affect the production of catfish in East Buay Madang District East OKU Regency and calculate the income of catfish farms in East Buay Madang District East OKU Regency. This research was conducted since November 2016 until January 2017. The research method used in this research is survey, that is the method used to obtain the data - data or facts that exist and looking for factual information. The type of data used in this study includes Primary data and Secondary data. The sampling method used is the census method taking the entire population for the sample of the study. The results showed that the factors - significant factors that influence seeds, feed and lime. While for the labor has no significant effect on the production of catfish culture in East Buay Madang district, due to the use of labor has been replaced by modern agricultural machinery tools that cause the unemployment of labor. The average income of catfish farming farmers is Rp.23.440 .313 / ha.